Practical problems in mathematics for health occupations - Simmers, Louise (Thomson/ Delmar Learning, 2005)
This newly revised book provides a strong foundation in the essential math processes that are employed by health occupations workers in all areas of health care. Exercises are presented in a word problem format with concrete examples of how the math process is used in different health care careers. Problems start with simple examples and progress to complex paradigms that induce readers to tackle difficult situations. In addition to basic applications with whole numbers, fractions, and decimals, information is also featured on common graphs, charts, and gauges that are likely to be encountered in the health care field. This edition includes a large portion of coverage that is devoted to problems involving medications, intravenous solutions, and other emulsions.